Th1 polarized response induced by intramuscular DNA-HSP65 immunization is preserved in experimental atherosclerosis - Fonseca, D. M.; Bonato, V. L. D.; Silva, C. L.; Sartori, Alexandrina [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 2007)
We previously reported that a DNA vaccine constructed with the heat shock protein (HSP65) gene from Mycobacterium leprae (DNA-HSP65) was protective and also therapeutic in experimental tuberculosis. By the intramuscular route, this vaccine elicited a predominant Th1 response that was consistent with its protective efficacy against tuberculosis. It has been suggested that the immune response to Hsp60/65 may be the link between exposure to microorganisms and increased cardiovascular risk. Additionally, the high cholesterol levels found in atherosclerosis could modulate host immunity. In this context, we evaluated if an atherogenic diet could modulate the immune response induced by the DNA-HSP65 vaccine. C57BL/6 mice (4-6 animals per group) were initially submitted to a protocol of atherosclerosis induction and then immunized by the intramuscular or intradermal route with 4 doses of 100 µg DNA-HSP65. on day 150 (15 days after the last immunization), the animals were sacrificed and antibodies and cytokines were determined. Vaccination by the intramuscular route induced high levels of anti-Hsp65 IgG2a antibodies, but not anti-Hsp65 IgG1 antibodies and a significant production of IL-6, IFN-g and IL-10, but not IL-5, indicating a Th1 profile. Immunization by the intradermal route triggered a mixed pattern (Th1/Th2) characterized by synthesis of anti-Hsp65 IgG2a and IgG1 antibodies and production of high levels of IL-5, IL-6, IL-10, and IFN-g. These results indicate that experimentally induced atherosclerosis did not affect the ability of DNA-HSP65 to induce a predominant Th1 response that is potentially protective against tuberculosis.
Keywords: DNA-HSP65; Genetic vaccine; Atherosclerosis; Tuberculosis; Th1; Cholesterol